Frequency and Prognostic Impact of Consistently Low Edmonton Symptom Assessment System Score in the Patients Treated with Palliative Radiotherapy - Nieder, Carsten (Cureus, 2018)
Introduction Our department's standard work-flow includes assessment of all the patients with the Edmonton Symptom Assessment System (ESAS), a one-sheet questionnaire addressing 11 major symptoms and wellbeing on a numeric scale of zero-10, before the palliative radiotherapy (PRT). Based on previous research, we hypothesized that the patients with minimal or moderate total symptom burden might have better overall survival after the PRT than those with at least one higher symptom score. Methods We performed a retrospective analysis of 94 patients and calculated actuarial survival from the first day of the PRT (Kaplan-Meier method). We identified the patients with the score zero for all ESAS items (no symptoms), at least one item with score one-two (minimal symptoms), and at least one item with the score three (moderate symptoms). Results High proportions of the patients had ESAS scores zero- two for nausea (80%), sadness/depression (65%) and constipation (64%). The mean values were often in the range of two-four. Only one patient reported scores of zero throughout the questionnaire. He was treated for hematuria, a symptom that is not part of the ESAS. Three patients reported scores of zero-two throughout the questionnaire. Except for the performance status zero-one, their baseline characteristics were heterogeneous. Two patients reported scores not exceeding three for all items. These patients had excellent performance status, too. None of the six patients (6%) with relatively low ESAS scores of zero-three received care by the hospital's multidisciplinary palliative team. Only one was using opioid analgesics. The median survival for this small subset of six patients was six months, identical to the result for all the patients with higher symptom burden (p = 0.62). Conclusion The proportion of the patients with ESAS scores zero-three throughout the questionnaire was 6%, which resulted in the limited statistical power for the survival comparisons. The survival outcomes were similar. Before PRT, 94% of the patients reported at least one ESAS item of severity four-10. The symptoms not included in the questionnaire, e.g., hematuria might result in erroneous assignment to the low-symptom-burden group and obscure the prognostic impact of low ESAS symptom burden.